Pengembangan Kemampuan Masyarakat Alue Dua Nisam Antara Terhadap Praktek Saham Syariah Melalui Aplikasi Android - Muhammad Yoesoef, Yoesrizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The socialization held in Alue Dua village Nisam Antara regency aims to improve the understanding of shares, especially Sharia stocks, especially for Alue Dua village Nisam Antara regency’s community in the district of North Aceh. The serviceman conducted socialization in Alue Dua village because located in a rural area. This devotion is undertaken from the interview result, which shows that many people do not understand the theory of stocks and how it works. Furthermore, most of Alue Dua village Nisam Antara regency community are reluctant to be investors in the stock market due to the lack of understanding about the difference between stocks in general and the Sharia one. The community considers that all forms of shares are illegal where the investment system is not following Shariah guidance. In this socialization activity, the serviceman explained the context of Sharia stocks and shares under the theory and its practice. Furthermore, the community is guided to jump directly becoming an investor by using the RTI Business application downloaded on the Playstore. The results show that Alue Dua village Nisam Antara regency community is very enthusiastic to join as a Sharia stock investor, evidenced by the answers given and expertise in using the RTI Business application.